2020
DOI: 10.1177/1758835920942367
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of cervical lymph node metastasis with contrast-enhanced ultrasound and association between presence of BRAFV600E and extrathyroidal extension in papillary thyroid carcinoma

Abstract: Objective: This study aimed to evaluate the correlation between cervical lymph node metastasis (CLNM) and each of the ultrasound features, immunohistochemical factors, and B-type Raf (BRAFV600E) mutation. Methods: A retrospective analysis was performed on 405 patients with single papillary thyroid carcinoma (PTC) nodules, all of whom underwent preoperative sonographic examinations, including gray-scale ultrasound, color Doppler ultrasound, and contrast-enhanced ultrasound (CEUS). All PTC patients were evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 38 publications
5
23
5
Order By: Relevance
“…In our study, hyper-enhancement on CEUS was correlated with cN1 rather than with microscopic pN1. The similar conclusion was drawn by other studies ( 7 , 10 ) that hyper-enhancement on CEUS suggested a high risk of LNMs. In these studies, the LNMs included both cN1 and microscopic pN1.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, hyper-enhancement on CEUS was correlated with cN1 rather than with microscopic pN1. The similar conclusion was drawn by other studies ( 7 , 10 ) that hyper-enhancement on CEUS suggested a high risk of LNMs. In these studies, the LNMs included both cN1 and microscopic pN1.…”
Section: Discussionsupporting
confidence: 90%
“…Some investigations ( 7 13 ) have explored the PTC’s US and CEUS features associated with LNMs and confirmed their values in predicting LNMs. However, LNMs could be stratified into clinical N1 (cN1, observed on US) and microscopic pN1 (pathological N1), which might bear different biological behavior and prognostic values.…”
Section: Introductionmentioning
confidence: 90%
“…Previous studies found that the enhancement patterns of PTC on CEUS are a useful tool to predict CLNM ( 29 , 30 ). Hong ( 31 ) et al.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Several studies have shown that CEUS could assess the biological behavior of thyroid nodules. [21][22][23] To our knowledge, few studies have included CEUS for preoperative prediction CLNM of different sized PTC.…”
Section: Introductionmentioning
confidence: 99%